A Journey to a Pioneer: Exploring Identity Transformations of a Rural Chinese EFL Teacher from a Social Ecological Perspective – An Autoethnographic Study - Huanling Xing; Liyan Liu; Anne Li Jiang (SAGE Open)
This autoethnographic study explores how the subjectively experienced ecological context of a rural Chinese EFL teacher facilitates the evolution of her teacher identity across three distinct phases. The focus is on examining the teacher’s transformation from a reality dissident to a realist, and ultimately to a pioneering educator while analyzing the factors that drive these shifts. The findings highlight the significant influence of the rural social context, closely linked to the teacher’s subjective experiences, and emphasize the critical role of core reflection in this process. This research offers valuable insights into the development of rural teachers’ professional identity, underscores the importance of understanding the complex interplay between the social environment and personal core qualities, and provides actionable implications for enhancing the professional growth and effectiveness of rural teachers.